(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A detailed Upper Cretaceous/Paleocene stratigraphic section was measured from the Spanboth Chu Valley, High Himalaya Nappes. Placement Of the Cretaceous—Tertiary boundary was refined, but some uncertitudes still remain because of poor exposure in this portion of the sequence. The Maastrichtian is characterized by floral and faunal assemblages consisting of Cymopolia, Ornphalocyclus, Siderolites and Odon togryphaea. The Lower Paleocene seems to be missing, whilst the Middle to Upper Paleocene is characterized by Rotalia, Daviesina, Lockhartia and Furcoporella assemblages. Sandstone petrography and carbonate microfacies were analyzed for environmental interpretation. Moreover, a reconsideration of the recent published data on the Upper Cretaceous/ Paleocene from the Zanskar mountains allows us to delineate a tentative depositional history of this part of the Indian continental margin during the considered time.